Fabrication of the alginate-combusted coal gangue composite for simultaneous and effective adsorption of Zn(II) and Mn(II). Issue 6 (December 2019) - Mohammadi, Ramin; Azadmehr, Amirreza; Maghsoudi, Abbas
Abstract: A combusted coal gangue is an inorganic waste utilized for removal of heavy metal from aqueous mixtures; however, the individual adsorption capacity of this adsorbent is not high individually. Therefore, a natural polysaccharide such as alginate is utilized to make bio- inorganic composite to increase the heavy metals' adsorption capacity. In this study, the alginate-combusted coal gangue (ACCG) composite was prepared and used as an adsorbent for Zn(II) and Mn(II) removal in batch experiments. The mineralogy, structure, and morphology of the ACCG composite were characterized. The principal parameters have been optimized, which in optimum condition, the maximum uptake of zinc and manganese was obtained 77.68 and 64.29 mg/g, respectively. To catch the mechanism of zinc and manganese adsorption, the equilibrium studies were investigated using nonlinear isotherm models in single and binary systems. The studies indicate that the adsorption process in both systems was carried out in a homogeneous and single layer surface. The amount of Zn(II) and Mn(II) adsorbed in competitive conditions were 65.4 and 53.8 mg/g, respectively. Kinetic studies indicate that intra-particle diffusion is the rate-limiting step of the adsorption process. Furthermore, thermodynamic studies demonstrated that the adsorption of zinc and manganese onto the ACCG composite was spontaneous.